2006
DOI: 10.1103/physrevb.73.220407
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of terahertz conductivity at the metal-insulator transition in doped manganites

Abstract: Magnetic field and temperature dependence of the Terahertz conductivity and permittivity of the colossal magnetoresistance manganite Pr0.65Ca0.28Sr0.07MnO3 (PCSMO) is investigated approaching the metal-to-insulator transition (MIT) from the insulating side. In the charge-ordered state of PCSMO both conductivity and dielectric permittivity increase as function of magnetic field and temperature. Universal scaling relationships ∆ε ∝ ∆σ are observed in a broad range of temperatures and magnetic fields. Similar sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
0
11
1
Order By: Relevance
“…Thus the negative susceptibility is considered to be originated by a magnetic resonance due to the internal magnetic anisotropy eld. 30 Tsutaoka et al reported this type of permeability spectra in a sintered yttrium iron garnet.…”
Section: Complex Permeability Behaviormentioning
confidence: 81%
“…Thus the negative susceptibility is considered to be originated by a magnetic resonance due to the internal magnetic anisotropy eld. 30 Tsutaoka et al reported this type of permeability spectra in a sintered yttrium iron garnet.…”
Section: Complex Permeability Behaviormentioning
confidence: 81%
“…5). 39 In Fig. 5 the parametric dependence of the dielectric permittivity is shown for various doping levels of La 1Àx Sr x MnO 3 .…”
Section: B Experiments With La 12x Sr X Mno 3 Compoundsmentioning
confidence: 99%
“…39 In Fig. 6 the dielectric permittivity of (Pr:Ca:Sr)MnO 3 is demonstrated as a function of conductivity.…”
Section: B Experiments With La 12x Sr X Mno 3 Compoundsmentioning
confidence: 99%
“…Many other materials showing dynamic THz responses applicable to active THz modulation also exist, such as NbO 2 , [211] InSb, [212,213] QWs, [214] titanium oxides, [215] orthoferrites, [216][217][218] rare-earth nickelates, [219][220][221] manganites, [222][223][224] topological insulators, [225][226][227] multiferroics, [228] molecular crystals, [229,230] medicines, [231] polymers, [232][233][234][235][236][237][238] and halide perovskites, [239][240][241][242][243][244][245][246] to name but a few. Considering the diversity of the material properties and the control mechanisms, plasmonic hybridization may bring about new possibilities for a wide variety of active THz devices.…”
Section: Potential Candidatesmentioning
confidence: 99%